Aktualisasi Nilai-Nilai Pendidikan Tauhid Bagi Peserta Didik Perspektif Al-Qur’an dalam Surat Al-Ikhlas dan Surat Luqman Ayat 13 - Silvia Supendi, Sinta; Hidayatullah; Wasehudin; Qurtubi, Ahmad; Fathurochman, Nanang (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The urgent need in education to swiftly promote Tauhid educational values among pupils motivates this research. Today, young people serve as excellent candidates for development and education. A child has the ability to absorb information into their fast-growing brains. Starting tauhid education during childhood will build a deep foundation in one's soul. Amidst the challenges of contemporary society, children are vulnerable to various dangers and adverse conditions. Once a child has firmly grasped the truth, they will naturally separate themselves from pure religious practices and consistently demonstrate behaviour worthy of praise, eventually maturing into obedient and respectful individuals. The letters that give a comprehensive explanation of the principle of Tauhid are Al-Ikhlas and Luqman verse 13. This is a letter in the Qur'an that serves as a proof of God's unity and a means of purifying and glorifying God, while also disputing every idea about His associates. The aim is to instill Tauhid values in the pupils. Those who do not believe in God do the things they do, and those who believe in Him do the things that He does. By promoting tauhid principles, we aim to develop tauhidi societies and prevent confusion with other beliefs. Both the great and the small are guilty when they associate with God.